Evaluation of a new variant in the aggrecan gene potentially associated with chondrodysplastic dwarfism in Miniature horses - de Andrade, Danilo Giorgi Abranches [UNESP]; Basso, Roberta Martins [UNESP]; Magro, Angelo José [UNESP]; Laufer-Amorim, Renée [UNESP]; Borges, Alexandre Secorun [UNESP]; de Oliveira-Filho, José Paes [UNESP] (Springer Nature, 2020)
Chondrodysplastic dwarfism in Miniature horses is an autosomal recessive disorder previously associated with four mutations (D1, D2, D3*, and D4) in the aggrecan (ACAN) gene. The aim of this study was to identify additional variants in the candidate ACAN gene associated with chondrodysplastic dwarfism in Miniature horses. Fifteen dwarf Miniature horses were found to possess only one of the dwarfism-causing variants, and two possessed none of the variants. The ACAN exons (EquCab3.0) of seven dwarf Miniature horses were sequenced. A missense SNP in coding exon 11 (g.95271115A > T, c.6465A > T—RefSeq XM_005602799.2), which resulted in the amino acid substitution p.Leu2155Phe (RefSeq XP_005602856.2), was initially associated with the dwarf phenotype. The variant was tested and found present in 14 dwarf foals as well as one parent of each, and both parents of a dwarf possessing two copies. Genetic testing of 347 phenotypically normal Miniature horses demonstrated that none had more than one of the dwarf alleles or c.6465A > T. However, a study of large breeds revealed the presence of c.6465A > T, which was present in homozygosis in two Mangalarga Marchador horses. We suggest that c.6465A > T as a marker of disequilibrium or complex interactions in the Miniature horse genome could contribute to the associated dwarfism.